1974
DOI: 10.1111/j.1432-1033.1974.tb03527.x
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase of Human Erythrocytes

Abstract: Hexokinase was purified 680-fold from erythrocytes of man. The preparation was not contaminated by other glycolytic enzymes.Initial reaction rate measurements were performed at pH 7.2, ionic strength 0.15 and 37 "C by use of coupled optical assays. The experimental data were used to construct a kinetic model of the enzyme, the kinetic parameters of which were estimated by means of a computer-fit program.The hexokinase of erythrocytes operates by a rapid-equilibrium random mechanism. The dissociation constant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…This is in agreement with the finding of Rapoport et al [43] that the concentration of ATP in erythrocytes incubated with glucose (Glc) at different pH values is constant ; this finding was also reported by Jacobasch et al [35]. Note, however that Minakami and Yoshikawa [37] have reported a pH-dependence of ATP concentration.…”
Section: Phsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with the finding of Rapoport et al [43] that the concentration of ATP in erythrocytes incubated with glucose (Glc) at different pH values is constant ; this finding was also reported by Jacobasch et al [35]. Note, however that Minakami and Yoshikawa [37] have reported a pH-dependence of ATP concentration.…”
Section: Phsupporting
confidence: 93%
“…At pH 6.9 Minakami and Yoshikawa [37] measured a decrease in glycolytic rate of 57 % relative to pH 7.2 ; a decrease of 55 % was predicted by the model. At pH 7.5, those authors measured an increase in glycolytic rate of 46 %, while the model predicted an increase of 53 %.…”
Section: Phmentioning
confidence: 88%
See 1 more Smart Citation
“…It is involved in glycolysis by its positive effects on phosphofructokinase [4] and pyruvate kinase [5] and by its inhibitory action on hexokinase [6,7]. The inhibition constants reported for hexokinase type I from human erythrocytes [6,7] are well in or below the range of the intracellular concentrations [l-3], suggesting a role for Glc-1 ,6-PZ in-regulation of hexokinase activity in vivo. In contrast Beitner et al [8] reported that Glc-1,6-P* exerted a selective inhibitory effect on hexokinase type II and had no effect on type I hexokinase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the inhibition by magnesium ions becomes visible only after the level of free ATP is negligible. With respect to the influence of magnesium ions, phosphofructokinase appears to differ from hexokinase [21] and pyruvate kinase [22] which show an activation by magnesium. However, there are some indications that the effect on pyruvate kinase is also essentially a deinhibition [23] of the enzyme caused by free ATP.…”
Section: Discussionmentioning
confidence: 99%